Teologi Tata Ruang: The Bridge Over Troubled Water - Manuahe, Yani Mick R. (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2024)
In the beginning God created space. But the fall of man made sin penetrate and destroy all existing life contexts. This article brings a breakthrough that assesses efforts to repair and maintain creation from a perspective that has received less attention. Cosmos space, exterior space, interior space, public space, private space, virtual space, even heart space, are parts that require a touch of arrangement. This article talks about the ecosystem living space which is currently facing the threat of destruction before our eyes, while the ecotheological struggle has not yet received accelerated application. God is the Arranger. So spatial planning theology, which connects basic conceptions to legal rules, will become a bridge as an alternative to overcome environmental damage, ethical degradation, application deadlocks and build human awareness about God, the Almighty Spatial Planner.